The Impact of Reluctance on Unilateral Contract - Jafar Salmanzadeh; Mostafa Abbasi (مطالعات فقه و حقوق اسلامی, 2018)
Invalidity is the prevailing theory about reluctant contracts and it is deemed a clear verdict in the Iranian legal literature. As common and recognized as the reluctant contract may be, the reluctant or involuntary unilateral contract is, on the other hand, vague, unfamiliar and subject of debate. Based on the unity of views and general principles of contract and unilateral obligation, some argue that similar to unilateral contracts, reluctant unilateral contracts must also be considered invalid; While the narrative evidence  points to the invalidity of unilateral divorces and releases  occurring under coercion. The present research aims at studying the quality and evidences of reluctant unilateral contract verdict.